AUTOMASI ALAT UJI TARIK TIPE TERCO MT 3017 BERBASIS MICROCONTROLLER - Franklin Tuerah; Markus Karamoy Umboh; Irvan Rondonuwu (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2020)
This research is to modify the TERCO MT3017 type tensile test equipment which is still manual by using supporting components of the Stepper Motor, Pressure Sensor and Distance Sensor, so that the tensile testing instrument is developed into a test tool that becomes more efficient in terms of object testing.The purpose of this research is to design and build automation Tensile Test Equipment based on a microcontroller, using a drive component and a pressure reader so that it can get more efficient data.The results obtained from the TERCO MT3017 type tensile testing tool are getting a composite test specimen diagram in general where the tensile force increases in accordance with the extension of the test specimen.Â Keywords: Tensile Test Equipment, Microcontroller, Stepper Motor